Stoddard Street looking towards Howard Street, 1894 - Unknown (Tufts Archival Research Center, 2005)
Street-level view southwest of Stoddard Street, looking towards Howard Street from the intersection of Stoddard and Court Streets. Signage adorns many of the buildings lining Stoddard Street, which is filled with pedestrians. Signage and street lamps adorn the facade of the Howard Athenaeum, which is located at 34 Howard Street at the far southwest end of Stoddard Street. Electricity lines and poles line Court Street and are included in the photograph. 7 1/2 x 4 3/4, 7 3/4 x 4 7/8 overall Photographs